The Gentle Side of the UPS: Ubiquitin-Proteasome System and the Regulation of the Myogenic Program - Olguín, Hugo C. (Frontiers in Cell and Developmental Biology, 2022)
In recent years, the ubiquitin-proteasome system (UPS) has emerged as an important regulator of stem cell function. Here we review recent findings indicating that UPS also plays critical roles in the biology of satellite cells, the muscle stem cell responsible for its maintenance and regeneration. While we focus our attention on the control of key transcriptional regulators of satellite cell function, we briefly discuss early studies suggesting the UPS participates more broadly in the regulation of satellite cell stemness and regenerative capacity.